The initial establishment and growth of Acacia mangium seedlings on compacted soils - Jusoff, Kamaruzaman; Awang, Kamis (1989)
Growth in height, diameter, leaf surface area, root and shoot was measured for 24 weeks on two week-old transplanted Acacia magnium Willd. Seedlings on compacted and non-compacted soils grown in a greenhouse. Significantly lower seedling height and diameter growth increment was attained on compacted soils compared to non-compacted soils. Compacted soils significantly reduced the mean total leaf surface area. Small differences in root growth characteristics were observed between A. mangium seedlings grown on compacted and non-compacted soils at harvest. Non-significant differences in root and shoot and dry weights and root/shoot ratio ws observed after harvest at week 24 for A. mangium seedlings grown on compacted and non-compacted greenhouse soils.